From ex vivo to in vitro models: towards a novel approach to investigate the efficacy of immunotherapies on exhausted Vγ9Vδ2 T cells? - Chauvet, Morgane; Bourges, Dorothée; Scotet, Emmanuel (Frontiers in Immunology, 2025)
Human γδ T cells demonstrate remarkable and diverse antitumor properties driven by TCR-dependent activation. Their non-alloreactive nature and pivotal role in cancer immunity position them as attractive targets for immunotherapies. However, upon infiltrating tumors, due to mechanisms induced by the tumor microenvironment’s immune evasion strategies, these cells frequently become exhausted, greatly weakening the efficacy and antitumor potential of novel immunotherapeutic treatments. While being extensively characterized in CD8+ T cells, research on γδ T cell exhaustion remains scarce. There is a growing need for comprehensive models to investigate the reinvigoration properties of exhausted γδ T cells. This review synthesizes current strategies and models for evaluating novel immunotherapies aimed at rejuvenating exhausted γδ T cells. It explores a progression of approaches, from ex vivo studies and in vivo murine models to emerging in vitro systems. The advantages and limitations of these models are discussed to provide a comprehensive understanding of their potential in advancing therapeutic research. Furthermore, recent findings suggesting in vitro exhaustion phenotypes closely mirror those observed ex vivo highlight opportunities for preclinical innovation. By refining these models, researchers can better optimize the immunotherapies targeting this unique T cell subset.